Peramalan Jumlah Kunjungan Wisatawan di Provinsi Nusa Tenggara Barat (NTB) Menggunakan Metode Arima Box-Jenkins - Soraya, Siti; Fitriana Aziza, Istin; Juanda, M. Rizky Ujiana; Primajati, Gilang; Rahima, Phyta (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2024)
The development of tourism in West Nusa Tenggara Province (NTB) is supported by geographical conditions with scattered small islands (gilis), tropical climate, and cultural peculiarities of the Sasak Tribe, thus becoming an attraction in the development of global tourist destinations. Tourism development in NTB Province will be more attractive with the establishment of the Mandalika National Tourism Development Strategic Area (KSPPN). NTB Province can maximize its role with the momentum of this strategic policy through the development of new growth centers based on the tourism sector, collaborating with other sectors, and packaging the potential of villages to become thematic tourism villages. A method to forecast the number of tourist visits in NTB Province is needed in assisting the government in preparing proper facilities and infrastructure if there is a possible surge in tourist visits. The method used in this study is the ARIMA Box-Jenkins Method to forecast the number of tourist visits in NTB Province. The data used in this study is in the form of secondary data sourced from the Central Bureau of Statistics of NTB Province, namely from January 2020 to December 2022. The results showed that the ARIMA model formed was (1,1,1), this shows that the forecasting of the number of tourist visits in NTB Province meets the assumption of white noise.